Influence of a multi-strain probiotic and zinc-glycine chelate, administered in ovo, on immune response in newly hatched chicks - Ciszewski, Artur; Jarosz, Łukasz S.; Grądzki, Zbigniew; Marek, Agnieszka; Kaczmarek, Beata; Hejdysz, Marcin; Rysiak, Anna (Frontiers in Physiology, 2025)
IntroductionThe supplementation of chicken embryos with bioactive compounds may elicit a beneficial effect on the development of their gut microbiome and enhance protection against infectious agents after hatching. Therefore, this study aimed to evaluate the effect of in ovo co-supplementation with a multi-strain probiotic and zinc-glycine chelate on the levels of pro- and anti-inflammatory cytokines, acute-phase proteins, and immunoglobulins in the peripheral blood and tissues of broiler chickens on the day of hatching and 7 days post hatching. The effect of supplementation on the growth parameters of chickens was assessed as well.MethodsThe study was conducted on 1,500 hatching eggs from a broiler breeding flock (Ross × Ross 308) at 36 weeks. ELISA kits were used to determine levels of acute-phase proteins and immunoglobulins. Expression of immunoglobulins was determined by means of qRT-PCR.ResultsThe results indicate enhanced synthesis of acute-phase proteins in the liver and increased levels of serum amyloid A in the small intestine tissue, as well as IgA and IgM mRNA and suppressed synthesis of pro-inflammatory cytokines IFN-γ and TNF-α. During the cumulative experimental period (days 0–42), the mean body weight gain (BWG) and feed intake (FI) in the group supplemented with a multi-strain probiotic were statistically significantly lower than the control group.DiscussionIt may be concluded that the combined in ovo use of a multi-strain probiotic and Zn-Gly chelate modulates the immune response, helps maintain the balance between the synthesis of Th1 and Th2 cytokines, inhibits inflammatory processes, and stimulates immune system development.